Estimating food quality from trade data: An empirical assessment - Daniele Curzi; Lucia Pacca; Alessandro Olper (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
Recent development in international trade theory gives growing emphasis to the quality of the exported products, showing that it affects both the direction of trade and the countries' export performances. However, as quality is unobservable, a measurement problem clearly emerges. In this paper we measure product quality relying on a nested logit demand structure developed by Berry (1994) and then applied to trade data by Khandelwal (2010). Our main goal is to investigate the reliability and the properties of this quality estimate, focusing on the EU food sector, where the growing attention on quality and safety issues have led to an increase in the demand for high quality products. Main results give credence to the accuracy of the quality estimates, which display some interesting properties. Indeed, the quality rankings we draw are in line with the expectations, and quality growth proves to be strongly correlated with TFP growth. Moreover, results reveal that the competitive strategy of countries, (high-quality vs. low-price) tends to change when moving from OECDs to non-OECDs. Finally, products quality proves to converge more rapidly in short than in long quality ladder markets. These results may have clear and interesting implications.
Keywords: 330; Quality estimates; Nested logit; Food products; International trade; EU market